Study of noscapine effects on rat hind paw inflammation induced by bradykinin and histamine - N Shiri; M Shafiei; SH Pashaeirad; M Mahmoudian (Institue of Medicinal Plants, ACECR, 2006)
Background: Noscapine is an isoquline alkaloid from opium with antitussive effect. Our previous study indicated that noscapine is non-competitive inhibitor of bradykinin. Objective: Since bradykinin and histamine contribute in inflammatory processes, the effect of noscapine on rat hind paw inflammation induced by bradykinin and histamine was investigated. Method: Paw edema induced by subplantar injection of 0.1 ml bradykinin solution (3nmol/paw) or 1% histamine solution. Noscapin (1, 5 and 10 mg/kg) and indomethacin (10mg/kg) as standard anti-inflammatory drug were administered intraperitoneally (i.p) one hour before injection of bradykinin or histamine. The thickness of hind paw was measured with a caliper and compared to control groups before and 15, 30, 60, 90, 120 minutes after injection of bradykinin and before and 60, 120, 180 minutes after injection of histamine. Results: Administration of noscapine significantly suppressed the inflammation. The maximum anti-inflammatory effect of noscapin observed at dose of 5 mg/kg against bradykinin and at dose of 10mg/kg against histamine. So this activity of noscapine was similar to activity of indomethacin. Conclution: Our results showed that noscapine has anti-inflammatory effect on inflammatory response of rat hind paw. This effect, was comparable to the anti-inflammatory effect of indomethacin.